Critical Factor Influencing Electronic Government Capacity Building in Sragen Municipality Government Public Service Delivery - Muhammad Shobaruddin (Magister Ilmu Administrasi Publik, 2018)
This study identifies critical factors in the capacity building of electronic government (e-government) in Sragen municipality, Indonesia. Sragen is a small city renowned as a pioneer in the implementation of e-government initiatives among other local governments. by conducted in-depth interview as well as observation thus the data was categorized and interpreted for fur-ther being discussed for the result. Results of the study showed that using an institutional ap-proach in e-government capacity building Sragen municipality succeeded in improving the quality and value of the relationship between government institutions and citizens; identified institutional factors that are crucial for successful e-government capacity building that include policies, organizational structure, and participatory public management.